Loss of Tifab , a del(5q) MDS gene, alters hematopoiesis through derepression of Toll-like receptor–TRAF6 signaling - Varney, Melinda E.; Niederkorn, Madeline; Konno, Hiroyasu; Matsumura, Takayuki; Gohda, Jin; Yoshida, Nobuaki; Akiyama, Taishin; Christie, Susanne; Fang, Jing; Miller, David; Jerez, Andres; Karsan, Aly; et al. (The Journal of experimental medicine, 2015)
TRAF-interacting protein with forkhead-associated domain B (TIFAB) is a haploinsufficient gene in del(5q) myelodysplastic syndrome (MDS). Deletion of Tifab results in progressive bone marrow (BM) and blood defects, including skewed hematopoietic stem/progenitor cell (HSPC) proportions and altered myeloid differentiation. A subset of mice transplanted with Tifab knockout (KO) HSPCs develop a BM failure with neutrophil dysplasia and cytopenia. In competitive transplants, Tifab KO HSPCs are out-competed by wild-type (WT) cells, suggesting a cell-intrinsic defect. Gene expression analysis of Tifab KO HSPCs identified dysregulation of immune-related signatures, and hypersensitivity to TLR4 stimulation. TIFAB forms a complex with TRAF6, a mediator of immune signaling, and reduces TRAF6 protein stability by a lysosome-dependent mechanism. In contrast, TIFAB loss increases TRAF6 protein and the dynamic range of TLR4 signaling, contributing to ineffective hematopoiesis. Moreover, combined deletion of TIFAB and miR-146a, two genes associated with del(5q) MDS/AML, results in a cooperative increase in TRAF6 expression and hematopoietic dysfunction. Re-expression of TIFAB in del(5q) MDS/AML cells results in attenuated TLR4 signaling and reduced viability. These findings underscore the importance of efficient regulation of innate immune/TRAF6 signaling within HSPCs by TIFAB, and its cooperation with miR-146a as it relates to the pathogenesis of hematopoietic malignancies, such as del(5q) MDS/AML.